Morphometric Examination of Paranasal Sinuses By Using CT Method - Kavaklı, Ahmet; Karakaş, Sacide (Fırat University, 2002)
Aim: A lot of variations may be noticed in shape and size in both paranasale sinuses. CT in diagnosis, although many studies were done, by using in these studies age groups were not usually established and the volumes of paranasale sinuses were not compared in detail. Therefore in this study, it was planned the, the relationship between right and left sides and the comparison of development progresses according to the age and sex with the results of the CT scans. Material and Method: Of all patients applied to radiology department, 91 cases without any paranasale sinuses pathology (like inflammation, operation or trauma) were selected for evaluation. Axial CT scans obtained from paranasale sinuses of all cases. In all scans the volumes of each area (maxillary sinus, frontal sinus, sphenoid sinus) were calculated and analysed statistically. Results and Conclusion: At the results, it was noticed that the volumes of paranasale sinuses increased with the age and women had lower mean volume. When we correlated right-left and ipsilateral structures (paranasale sinuses), it was determined that there was a positive correlation between them. The mean volumes were similar to the results on the literature.

Amaç: Sinus Paranasales şekil ve büyüklük açısından birçok farklılıklar gösterebilir. Bilgisayarlı tomografi (BT)'nin tanıda kullanılmasından sonra bu konuda çalışmalar yapılmış olmasına karşın, yapılan çalışmalarda genellikle yaş grupları oluşturulmamış ve sinus paranasales hacimleri birbirleri ile geniş şekilde karşılaştırılmamışlar. Bu nedenle BT kullanarak elde ettiğimiz verilerden, yaş - cinsiyete göre gelişme seyirlerini, sağ-sol taraf arasındaki ilişkileri araştırmayı planladık. Gereç ve Yöntem: BT tetkiki için Radyoloji Anabilim Dalına başvuran, herhangi bir patolojisi (geçirilmiş enfeksiyon, ameliyat veya travma) olmayan toplam 91 olgu (47 erkek, 44 kadın) seçildi. Her olguya sinus paranasales aksiyel BT tetkiki yapıldı. Elde edilen her kesitte ilgili bölgelerin (sinus maxillaris, sinus frontalis ve sinüs sphenoidalis) hacimleri ayrı ayrı hesaplandı ve istatistiksel analiz yapıldı. Bulgular ve Sonuç: Yapılan analizler sonucunda sinus paranasales hacimlerinin yaşla birlikte düzenli olarak arttığı, bunun yanında kadınların erkeklerden daha düşük hacım ortalamalarına sahip olduğu görüldü. Sağ-sol ve aynı taraftaki sinüs paranasales hacim ortalamaları yönünden baktığımızda pozitif yönde bir ilişki olduğu tespit edildi. Elde edilen hacim ortalamaları kaynaklarla karşılaştırıldığında verilerin birbirlerine yakın oldukları görüldü.
PARANASAL SİNUS'LARIN BİLGİSAYARLI TOMOGRAFİ YÖNTEMİYLE MORFOMETRİK İNCELENMESİ